Clinical significance of HDAC9 in hepatocellular carcinoma - Hu, Yuzhi; Sun, Lei; Tao, Shaofu; Dai, Min; Wang, Yandong; Li, Yong; Wu, Jiebin (Cellular and Molecular Biology, 2019)
In recent years, most related studies have found that chronic hepatitis B virus infection is the main cause of hepatocellular carcinoma (HCC), but the specific pathogenesis is still unclear. To investigate the function of HDAC in hepatocellular carcinoma (HCC), this study used qRT-PCR to determine the expression levels of miR-376a and HDAC9 mNRA in HCC and para-cancerous tissues. The clinical significance of HDAC9 in HCC was assessed in a study cohort containing 37 patients with HCC using immunohistochemistry. The expression level of miR-376a in liver cancer tissues was significantly lower than that in para-cancerous tissues, while the expression level of HDAC9 mRNA in liver cancer tissue was significantly higher than that in para-cancerous tissues. The expression of HDAC9 occurred mainly in the nucleus. There was a significant correlation between tumor differentiation and HDAC9. Survival analysis showed that HCC patients with higher HDAC9 expression had poorer prognosis, and subsequent multivariate analysis showed that HDAC9 expression level was an independent predictor. There was a definite correlation between HDAC9 and the expressions of AFP and Ki67. These results suggest that the expression level of HDAC9 in HCC is abnormally high while the expression level of miR-376a is significantly decreased, indicating that HDAC9 may be a potential prognostic indicator of HCC.